Seasonal variation in activity budgets of critically endangered Bornean banded langur, Presbytis chrysomelas chrysomelas in Malaysian Borneo - Nur Aizatul Izzati, Tukiman; Mohd Ridwan, Abd Rahman; Noor Faezah, Mohammad; Roberta Chaya Tawie, Tingga; Mohamad Bukhori, Mohamad Fhaizal; Mohd Azlan, Jayasilan; Denel, Azroie; ABDUL-LATIFF, MUHAMMAD ABU BAKAR; Md-Zain, Badrul Munir (Pensoft Publishers, 2025)
The activity budget of a primate varies in response to environmental and habitat conditions, including seasonality. To elucidate how primates adapt their behavior to the seasonal shift, the activity budget of Bornean banded langurs (Presbytis chrysomelas chrysomelas) in the Tanjung Datu National Park southwestern of Sarawak and stratum utilization were studied from July 2023 to February 2024. The behavioral data were collected through scan sampling (336 observation hours) of Bornean banded langur groups. Overall, the langurs allocated most of their time to resting (35.4%), feeding (32.3%), moving (16.2%), vocalizing (9.2%), and social activities like grooming and playing (6.9%). The seasonal variation was evident, with increased foraging and social activities during the dry season and a greater allocation of time to locomotion during the wet season. Additionally, the Mann-Whitney U test revealed significant seasonal fluctuation in social activities (grooming and playing, P<0.001), while feeding, moving, and resting remained unaffected (P>0.05). Food availability and distribution may influence the langur activity budget, with increased travel distance during the wet season because of food scarcity. The langurs predominantly use stratum C (21–30 m) to feed, rest, move, and socialize. This study highlights the seasonal ecology of this critically endangered endemic primate and underscores the importance of habitat conservation efforts to ensure the sustainability of their populations amid environmental changes.